2005
DOI: 10.12693/aphyspola.108.837
|View full text |Cite
|
Sign up to set email alerts
|

Hole Scattering in GaSb: Scattering on Space Charge Regions Versus Dipole Scattering

Abstract: Hole concentration and mobility were investigated by Hall measurements in nominally undoped p-type GaSb in the temperature range from 77 to 300 K. The dependence of the thermal ionization energy of native acceptors on the acceptor centre concentration and on the compensation degree was determined. The temperature dependence of the hole mobility was analyzed using a heuristic semi-empirical model as well as using a phenomenological two-hole band model. Space charge scattering and/or dipole scattering described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Van der Pauw Hall data were measured between 300 K and 77 K on 18 samples of undoped p-type bulk grown GaSb obtained from three different sources [3,4] as well as on samples of InP:Zn bulk crystals obtained from two different sources [5]. The room temperature hole concentration of the GaSb samples studied was in the range from 6x10 16 cm -3 to 1x10 18 cm -3 , the corresponding Hall mobility was between 420 cm 2 /Vs and 660 cm 2 /Vs at 300 K and between 400 cm 2 /Vs and 2300 cm 2 /Vs at 77 K. The room temperature hole concentration of the InP samples studied was in the range from 2x10 17 cm -3 to 5x10 18 cm -3 , the corresponding Hall mobility was between 45 cm 2 /Vs and 100 cm 2 /Vs.…”
Section: Measurements and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Van der Pauw Hall data were measured between 300 K and 77 K on 18 samples of undoped p-type bulk grown GaSb obtained from three different sources [3,4] as well as on samples of InP:Zn bulk crystals obtained from two different sources [5]. The room temperature hole concentration of the GaSb samples studied was in the range from 6x10 16 cm -3 to 1x10 18 cm -3 , the corresponding Hall mobility was between 420 cm 2 /Vs and 660 cm 2 /Vs at 300 K and between 400 cm 2 /Vs and 2300 cm 2 /Vs at 77 K. The room temperature hole concentration of the InP samples studied was in the range from 2x10 17 cm -3 to 5x10 18 cm -3 , the corresponding Hall mobility was between 45 cm 2 /Vs and 100 cm 2 /Vs.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…From this analysis the acceptor and donor concentrations which are the relevant input parameters in the mobility analysis, were deduced [4,5]. It was found that all samples measured were characterized by a substantial compensation degree, K > 0.5.…”
Section: Mobility Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations